Recent Advances in Understanding the Role of IKKβ in Cardiometabolic Diseases - Hernandez, Rebecca; Zhou, Changcheng (Frontiers in Cardiovascular Medicine, 2021)
Cardiometabolic diseases, including cardiovascular disease, obesity, and diabetes, are the leading cause of mortality and morbidity worldwide. Cardiometabolic diseases are associated with many overlapping metabolic syndromes such as hypertension, hyperlipidemia, insulin resistance, and central adiposity. However, the underlying causes of cardiometabolic diseases and associated syndromes remain poorly understood. Within the past couple of decades, considerable progresses have been made to understand the role of inflammatory signaling in the pathogenesis of cardiometabolic diseases. The transcription factor, NF-κB, a master regulator of the innate and adaptive immune responses, is highly active in cardiometabolic diseases. IκB kinase β (IKKβ), the predominant catalytic subunit of the IKK complex, is required for canonical activation of NF-κB, and has been implicated as the critical molecular link between inflammation and cardiometabolic diseases. Recent studies have revealed that IKKβ has diverse and unexpected roles in mediating adiposity, insulin sensitivity, glucose homeostasis, vascular function, and atherogenesis through complex mechanisms. IKKβ has been demonstrated as a critical player in the development of cardiometabolic diseases and is implicated as a promising therapeutic target. This review summarizes current knowledge of the functions of IKKβ in mediating the development and progression of cardiometabolic diseases.